Augšzemnieku dialekta dziļās latgaliskās izloksnes Ziemeļaustrumvidzemē (t. s. Malēnijā) - Markus, Dace (Baltistica, 2012)
THE DEEP LATGALIAN VARIANTS OF THE HIGH LATVIAN DIALECT IN NORTH-EAST VIDZEME (SO-CALLED MALENIA)SummaryThe author of the article analyses the differences in phonetics between the deep Latgalian (the so-called Malenian) variants of the High Latvian dialect, which is spoken in North-East Vidzeme, and other deep Latgalian variants. The most characteristic feature of the Malenian variant of the dialect is its explicitly and sharply broken syllable intonation standing out even more due to the lack of consonant palatalisation in the above dialect variants, which is why it sounds even harder when pronounced than it does when other deep Latgalian variants are spoken. The alteration of a into o in the prefix aiz- (for instance, oizskrīt ‘aizskriet’) is characteristic of the Malenian variants only because such an alteration does not take place in other deep Latgalian variants.Younger generations are no longer so skillful in speaking the variant. The samples collected and analysed during the recent years indicate that there are pronunciation inconsistencies in the variants under study. The impact mainly comes from the standard language and, possibly, from other Latgalian variants that sound similar. The process is encouraged by contacts with the speakers of the neighbouring variants as well as Latgalian texts and songs often broadcast on the radio and television.Nevertheless, there is a common understanding that the so-called Malenian variants bearing no official name have preserved phonetic peculiarities that distinguish them from the other deep Latgalian variants.
Keywords: dialectology; High Latvian; Malēnija; phonetics